Public-private collaboration in European cybersecurity. Between organizational and regulatory plans - Castaldo, Francesca; Serini, Federico (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2024)
Bringing together considerations straddling organizational business science and public law, the paper aims to provide a multidisciplinary overview of public-private collaboration in the context of cybersecurity. Two profiles are analysed: the public-private partnership, an organizational and legal perspective, and the phenomenon of co-regulation in cyber security technical standardization and certification. The study of the two profiles just mentioned will allow us to analyse the role of private parties, in one case as recipients of the cybersecurity obligations of secondary legislation then translated at the national level, and on the other as actors who promote and participate in the elaboration of technical cyber security standards. The opportunity is to contextualize said phenomenon, as well as to grasp its ongoing evolutionary profiles and criticalities.